(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Ayurveda is an ancient holistic medical system that emphasizes personalized health and well-being. As one of the oldest healing traditions, it includes a vast body of medical knowledge, concepts, and practices developed over thousands of years. Ayurveda includes eight main branches, one of which is Agada Tantra, a specialized field that deals with the identification and treatment of toxins-both living (such as snake venom) and non-living (such as chemical poisons)-and the management of toxin-related illnesses, known as Visha diseases. Agada Tantra in Ayurveda embodies a holistic and unified method for treating poisoning. It combines ancient knowledge with modern therapeutic practices, providing a useful resource for managing toxicological emergencies. Kerala has a strong heritage in toxicology, deeply embedded in its ancient Ayurvedic texts and traditional practices. The "Visha Vaidya Jyotsanika" is a well-known Malayalam text dedicated to Visha Chikitsa (toxicology), providing important information on different formulations and practical approaches used in treatment. Nalpamaramadhukadhi lepa is a formulation serves as a potent remedy mentioned in this text for counter acting poisons. This study highlights the ingredients, preparation method, therapeutic uses, and effectiveness of the formulation.